EVALUATION AND OPTIMIZATION OF CUTTING EFFICIENCY OF MOTORIZED SOYBEAN HARVESTER - Ugama, Godwin Nkuma; Mohammed, Usman Suleiman; Isiaka, Moshudi; Abdulsalam, Mohammad (FUDMA Journal of Sciences, 2026)
A motorized soybean harvester was designed and evaluated on a soybean farm to determine its cutting efficiency. Three independent factors at five levels were used. Moisture content (9, 14,18,22, and 26 %), clearance between the cutting blades (0.4, 2, 4, 6 and 8 mm). The experimental design was carried using Design of Expert version 13.0. The total number runs were 36, and each plot measured 4 m by 4 m. In each plot, the variation the factors were established on the machine before cutting soybeans. After cutting each plot, the harvester was stopped, and the number cut and uncut soybean stem were counted and recorded. Thereafter, the data generated was subjected to statistical analysis. The ANOVA results showed that moisture content and cutter bar speed had significant effect of 0.0001 each on the cutting efficiency at 5 % confidence interval. Further analysis with 3D response surface graph, and 2D contour plot revealed that optimum cutting efficiency was achieved at 18 % moisture content, 4 mm clearance between the cutting blades, and 850 rpm cutter bar speed. I addition, numerical optimization alongside with ramp function graph and desirability bar chart were used to optimize the harvester, and it revealed that cutting efficiency of 77.302 % can can be achieved if the moisture content was set at 14 %, clearance between the cutting blades at 4.17 mm, and cutter bar speed at 1200 rpm. In essence, the cutting efficiency of the motorized soybean harvester is above average.
Keywords: Moisture content; 3D; Efficiency; Experimental; Desirability